KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN BAHASA INDONESIA - Basuki Basuki; Yulinda Erma Suryani; Dwi Bambang P Setiadi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstractThis study aims to describe students’ learning difficulties in the Indonesian language learning process at the senior high school. The research subjects were students of SMAN1 Klaten, SMAN 1 Karangnongko, and SMAN 1 Karangdowo. The data were collectedby means of tests and interviews. They were analyzed using qualitative and quantitativedescriptive techniques with the AnBuso computer program. The results of the dataanalysis show that the students have difficulties in: the language sub-competenciesof structure (61.07%) and vocabulary (52.6%); the language competencies of listening(41.88%), speaking (18.89%), reading (21.15%), and writing (20.02%); and the literarycompetency at the levels of information (45.69%), concepts (40.9%), perspectives (41.74%),and appreciation (47.1%). These show that the difficulties are evenly distributed on thevarious components of learning materials, both for language and literary competencies, sothat the solutions must be comprehensive including the selection of learning methods.Keywords: learning difficulties, competencies, Indonesian language